Exploring N-Back Cognitive Training for Children With ADHD. Issue 5 (March 2020) - Jones, Masha R.; Katz, Benjamin; Buschkuehl, Martin; Jaeggi, Susanne M.; Shah, Priti
Objective: The efficacy of n -back training for children with attention deficit hyperactivity disorder (ADHD) was tested in a randomized controlled trial.Method: 41 children aged 7 to 14 years with ADHD were trained on an n -back task, and their performance was compared with that of an active control group ( n = 39) who were trained on a general knowledge and vocabulary task.Results: The experimental group demonstrated transfer of training to a nontrained n -back task as well as to a measure of inhibitory control. These effects were correlated with the magnitude of training gains.Conclusion: Our results suggest that n -back training may be useful in addressing some of the cognitive and behavioral issues associated with ADHD.